Educational Booklet Effect on Knowledge and practice of Osteoporotic Patients - Z Komeilian; M Sedaghat; R Baradar Jalil; M Arzaghi; Y Jaladat; B Larijani (Tehran University of Medical Sciences, 2004)
Osteoporosis is a common and asymptomatic disease. Fifty percent of men and 70% of women over 50 years are affected by osteoporosis or osteopenia. The disease and its complications can be prevented by raising society knowledge throughout education. The aim of this study was determining the effect of educational booklet on Knowledge & Practice of osteoporotic patients who were referred to Shariati Hospital. This was an experimental and self-control study in which the knowledge and practice was determined by standard questionnaire (face to face interview before education and telephone-route after education). Data were analyzed by Mann-Whitney U test. Three hundred and fourty patients coming to Shariati Hospital osteoporosis clinic were investigated. Educational booklet raised society knowledge and practice up to 24% and 16%, respectively. The results showed that educational booklets were not effective tools to increase knowledge and practice of the patients. We recommend other educational tools like meetings, posters, and Philip charts, to enable patients to take care of themselves optimally.